18 Differences in quantitative myocardial perfusion mapping by CMR at 1.5T and 3T. (28th January 2023) - Abraham, George; Hoole, Stephen; Berry, Colin; Weir-McCall, Jonathan
Abstract : Introduction: Quantitative myocardial perfusion mapping by CMR is an emerging non-invasive diagnostic tool for ischemia. CMR derived stress myocardial blood flow (MBF) and myocardial perfusion reserve (MPR) have been validated against invasive coronary guidewire tests in epicardial and microvascular coronary disease however it is not clear the impact of field strength (3T vs 1.5T) on flow quantitation. Materials and Methods: We performed a retrospective analysis of 178 clinical adenosine stress CMR scans with automated inline perfusion mapping at 1.5T (79 patients) and 3T (99 patients), comparing global stress and resting MBF, stress endocardial:epicardial ratio and MPR. The cardiac diagnosis was coded for each patient as follows: normal, ischemia with no obstructive coronary disease (INOCA), epicardial coronary artery disease (CAD) with ischemia, CAD without ischemia and non-ischemic cardiomyopathy. Results: Resting MBF was significantly higher at 1.5T versus 3T after adjustment for baseline rate-pressure product, gender and cardiac diagnosis (0.72±0.31 vs. 0.60±0.38 ml/g/min, p=0.01). Mean stress MBF was also higher at 1.5T versus 3T however the difference was not statistically significant (stress MBF: 1.81±0.70 ml/g/min vs. 1.64±0.67 ml/g/min, p=0.11). Endocardial: epicardial ratio (0.87±0.15 vs. 0.88±0.12, p=0.63) and MPR (2.70±1.01 vs. 2.95±0.91, p=0.09) were not significantly different at 1.5T versus 3T. Amongst the 70 scans coded as 'normal', significant differences in resting MBF persisted (1.5T: 0.82±0.39 ml/g/min vs. 3T: 0.59±0.17 ml/g/min, p=0.01), while there were non-significant differences between other variables. Discussion: Diagnostic cut-offs for MPR and stress MBF have been suggested for the non-invasive assessment of obstructive CAD and INOCA by CMR. Our study shows that adjusting for differences using ratios (MPR and endocardial:epicardial ratio) rather than absolute values is robust and transferrable across field strengths. Resting MBF was higher at 1.5T even after adjustment for hemodynamic status however further investigation is required to determine if normal cut-offs for absolute quantification require adjustment for magnetic field strength before routine clinical use. Conclusion: Quantitative myocardial perfusion mapping detects higher MBF values at 1.5T compared with 3T field strength, however MPR is robust to this effect. Acknowledgements: The authors would like to thank the patients and staff of Royal Papworth Hospital NHS Foundation Trust. GA, SPH are supported by a research grant from The Jon Moulton Charity Trust and an NIHR Cambridge Biomedical Research Centre Biomedical Resources Grant (University of Cambridge, Cardiovascular Theme, RG64226).